Kondo interaction in FeTe and its potential role in the magnetic order - Younsik Kim; Min-Seok Kim; Dongwook Kim; Minjae Kim; Minsoo Kim; Cheng-Maw Cheng; Joonyoung Choi; Saegyeol Jung; Donghui Lu; Jong Hyuk Kim; Soohyun Cho; Dongjoon Song; et al. (Nature Communications, 2023)
Abstract Finding d-electron heavy fermion states has been an important topic as the diversity in d-electron materials can lead to many exotic Kondo effect-related phenomena or new states of matter such as correlation-driven topological Kondo insulator. Yet, obtaining direct spectroscopic evidence for a d-electron heavy fermion system has been elusive to date. Here, we report the observation of Kondo lattice behavior in an antiferromagnetic metal, FeTe, via angle-resolved photoemission spectroscopy, scanning tunneling spectroscopy and transport property measurements. The Kondo lattice behavior is represented by the emergence of a sharp quasiparticle and Fano-type tunneling spectra at low temperatures. The transport property measurements confirm the low-temperature Fermi liquid behavior and reveal successive coherent-incoherent crossover upon increasing temperature. We interpret the Kondo lattice behavior as a result of hybridization between localized Fe 3dxy and itinerant Te 5pz orbitals. Our observations strongly suggest unusual cooperation between Kondo lattice behavior and long-range magnetic order.